Formulation And Evaluation Sunflower Seed Oil With Sappan Wood Extract (Caesalpinia Sappan) Lip Balm - Anugerah Suciati; Diah Ayu Mutmaina; Nurul Marfu’ah (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2024)
Lip balm preparations can be used to prevent and treat chapped lips due to UV exposure and synthetic ingredients. Natural ingredients such as sappan wood extract and sunflower seed oil can be used to reduce the use of synthetic ingredients. The brazilin compound in sappan wood has anti-free radical, antibacterial, and anti-inflammatory abilities. While chlorogenic type polyphenol compounds in sunflower seeds have potential as antioxidants. The purpose of this study was to make a lip balm preparation of a combination of sunflower seed oil with sappan wood extract. This research is an experimental research by extracting sappan wood using the socletation method and 70% ethanol solvent. Lip balm preparations were made from a combination of sunflower seed oil: secang wood extract in the ratio of 5%:1,25% (F1), 10%:2.5% (F2) and 15%:3,75% (F3). Evaluation of the preparation includes organoleptic test, homogeneity, pH, spreadability, adhesiveness, melting point, and moisture capacity. While the results of the stability test were analyzed using the paired t-test parametric test with SPSS 24.0 and a significance level of 95%. The results showed that the characteristics of the lip balm preparation of a combination of sunflower seeds and sappan wood extract showed results in organoleptic testing, namely having a yellowish beige and yellow color. The aroma is typical of beeswax with an oily semi-solid texture. The lip balm preparation shows that all preparations are homogeneous, with pH test results of 4.90-6.12; leachability of the lip balm.